1997
DOI: 10.1302/0301-620x.79b4.7316
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of sinus-track cultures in chronic bone infection

Abstract: Sinus-track cultures were compared prospectively with cultures from operative specimens in 55 patients with chronic bone infection. There was a total of 115 operative isolates; 102 of the sinus-track isolates were identical (88.7%), showing a specificity of 95.7% and a predictive value of 90.3%. A sinus-track specimen proved to be a reliable source for the isolation of all bacteria causing chronic bone infection except Staphylococcus epidermidis, provided that material from the depths of the sinus was aspirate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
11
0

Year Published

2006
2006
2016
2016

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(11 citation statements)
references
References 11 publications
0
11
0
Order By: Relevance
“…Since the pathologically dislocated hips generally did not become normal spontaneously during growth, detection at early stage was necessary and then appropriate remedial measures were performed [8,9]. If the abducted femoral head was hinged on the acetabular margin, which was common in subluxated and dislocated hips, spontaneous progressive cephalocotyloid improvement could not be expected without having a non-hinging hip by any measure.…”
Section: Discussionmentioning
confidence: 99%
“…Since the pathologically dislocated hips generally did not become normal spontaneously during growth, detection at early stage was necessary and then appropriate remedial measures were performed [8,9]. If the abducted femoral head was hinged on the acetabular margin, which was common in subluxated and dislocated hips, spontaneous progressive cephalocotyloid improvement could not be expected without having a non-hinging hip by any measure.…”
Section: Discussionmentioning
confidence: 99%
“…In reality, this situation would likely concern only a minority of cases. In no way should deep ulcer specimens from the bone surface should replace bone cultures in situations where biopsy can be readily obtained, because bone cultures together with histology remain the gold standard for the diagnosis of osteomyelitis [1][2][3][4][5][6][7][8][9]11]. Further trials are needed to confirm our findings.…”
mentioning
confidence: 94%
“…Superficial wound swabbing has been proven inadequate for predicting the infecting microorganisms [1,2]. However, several studies investigated the accuracy of consecutive deep sinus tract cultures compared to bone biopsy [3][4][5][6][7][8][9]. In cases of monomicrobial osteomyelitis with sinus tract, concordant tract cultures with bone contact accurately predicted the pathogen of bone cultures [3,[6][7][8], which, however, was not unanimously confirmed [4,5,9].…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Prevotela melaninogenica and Peptostreptococcus species were the predominant anaerobic causative agents. Two studies were carried out by Mousa (1997) and Mousa et al (1996) concerning anaerobic bacterial infection. They found that the high rate of recovery of anaerobes was related to immediate inoculation and cultivation of material under anaerobic condition by bedside whilst delayed handling of the specimens may lead to loss of strict anaerobes.…”
Section: Aerobicmentioning
confidence: 99%